Eidos System Prediction of Myopia in Children in Early Education Stages - Abdullah M. Al-Ansi; Mudar Almadi; Parul Ichhpujani; Vladimir Ryabtsev (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2023)
This study used a database containing factors that, when processed using the Eidos intellectual system, detect myopia in children of primary school age. The database includes parameters that take into account the properties of the visual system, as well as factors that determine the duration of the performance of the main functions of the cognitive and entertaining nature of the students. The results obtained allow us to determine those factors that are more conducive to the appearance of myopia. The negative impact of some factors that cause myopia can be removed, such as, limiting the screen time spent, increasing outdoor activities/sports. A retrospective training sample can be used for automated processing using the Eidos intellectual system of the results obtained during the preventive examination of schoolchildren by an ophthalmologist. Early intervention towards myopia management in students, improves the chances of maintaining vision and slows myopia progression. The contribution of this research includes factors of a social nature that could be influenced at school in the process of education, increasing the attention towards childent, awareness of maintaining vision and slows down the progression of myopia.